Abundance, chemical composition and lead adsorption properties of sedimentary colloids in a eutrophic shallow lake. (March 2019) - Xu, Huacheng; Ji, Li; Kong, Ming; Xu, Mengwen; Lv, Xizhi
Abstract: Colloidal particles are omnipresent in lake sediments and substantially influence the retention, transportation, and fate of contaminants in lake ecosystems. In this study, the abundance, chemical composition and adsorption behavior of sedimentary colloids (including total and inorganic colloids) from different ecological regions, were for the first time investigated via ultrasonic extraction, spectral analysis and batch absorption experiments. Results showed that the extraction efficiencies of sedimentary colloids showed an ultrasonic energy-dependent enhancement, and the algae-dominated area contained comparable colloidal abundance with the macrophyte-dominated area (i.e., 198.5 vs. 183.3 mg/g). Despite the different ecosystems, these sedimentary colloids usually had a wide size distribution of 30–200 nm, and were characterized with montmorillonite-, kaolin-, volkonskoite-, and quartz-rich chemical compositions. Batch experiment showed that the total pristine colloids exhibited higher adsorption capacity for Pb(II) than the inorganic colloids both for the macrophyte- and algae-dominated sediments, and the adsorption process followed pseudo-second-order kinetics and Langmuir isotherm, irrespective of different colloidal types. Thus, sedimentary colloids can immobilize the heavy metals in sediment and decrease their release into the water column, which can be considered as a sink for contaminants. This study highlighted the significance of sedimentary colloids in determining the physicochemical properties of lake sediments and in evaluating the environmental behavior and fate of contaminants in lake ecosystems. Highlights: Abundance, composition and adsorption properties of sedimentary colloids were studied. The ultrasonic-induced extraction efficiency enhancement was related to colloidal composition and sediment type. Sedimentary colloids had Fe-, Al- and Si-containing mineralogical structures with various conformations. Total colloids exhibited higher adsorption capacity for Pb(II) than the inorganic colloids. Langmuir isotherm, pseudo-second-order kinetics, and chemical mechanism accounted for the adsorption process.